Kedah tennis back in the spotlight: Newly appointed officials organise successful three-day tournament - Noh, Dasheer (The Star, 2013)
THE Kedah Tennis Association's (KTA) decade-old hibernation finally ended when a new set of officials led by president Dr Kamarulzaman Ismail and secretary Samsul Kamil Osman successfully organised the Kedah-Wilson Junior tournament.